Correlation between androgen receptor expression and FGF8 mRNA levels in patients with prostate cancer and benign prostatic hypertrophy. Issue 1 (1st January 1999) - Wang, Q; Stamp, G W; Powell, S; Abel, P; Laniado, M; Mahony, C; Lalani, E N; Waxman, J
Abstract : AIM: To investigate the correlation between androgen receptor expression and fibroblast growth factor 8 (FGF8) mRNA levels. METHODS: 39 human prostate cancers and 14 benign prostatic hypertrophy specimens were examined immunohistochemically for androgen receptor expression and by in situ hybridisation and reverse transcription polymerase chain reaction for FGF8 expression. RESULTS: In 39 tumours there was a statistically significant negative correlation between tumour grade and FGF8 expression and a positive correlation between FGF8 and androgen receptor expression. All 14 benign hypertrophy specimens expressed moderate to high levels of FGF8 and androgen receptor. CONCLUSIONS: Loss of FGF8 may be a factor involved in the development of prostatic cancer.